An Alcohol Dehydrogenase Gene from Synechocystis sp. Confers Salt Tolerance in Transgenic Tobacco - Yi, So Young; Ku, Seong Sub; Sim, Hee-Jung; Kim, Sang-Kyu; Park, Ji Hyun; Lyu, Jae Il; So, Eun Jin; Choi, So Yeon; Kim, Jonghyun; Ahn, Myung Suk; Kim, Suk Weon; Park, Hyunwoo; et al. (Frontiers in Plant Science, 2017)
A Synechocystis salt-responsive gene 1 (sysr1) was engineered for expression in higher plants. Gene construction was stably incorporated into tobacco plants. We investigated the role of Sysr1 [a member of the alcohol dehydrogenase (ADH) superfamily] by examining the salt tolerance of sysr1-overexpressing (sysr1-OX) tobacco plants using qRT-PCR, GC-MS, and bioassays. The sysr1-OX plants exhibited considerably increased ADH activity and tolerance to salt stress conditions. Additionally, the expression of several stress-responsive genes was upregulated. Moreover, airborne signals from salt-stressed sysr1-OX plants triggered salinity tolerance in neighboring wild-type (WT) plants. Sysr1 reduces aldehydes to alcohols, which may affect the quality of green leaf volatiles in sysr1-OX plants. Actually, the Z-3-hexenol level was approximately 2-fold higher in sysr1-OX plants than in WT plants within 1-2h of wounding. Furthermore, analyses of WT plants treated with vaporized green leaf volatiles indicated that Z-3-hexenol was stronger inducers of stress-related gene expression and salt tolerance than E-2-hexenal. Therefore, it is consider that the increase of C6 alcohol, Z-3-hexenol induces the expression of the resistance gene, thereby enhancing the salt tolerance of the transgenic plant. Our study reveals a role for ADH gene in salinity stress responses and provides a genetic engineering strategy to improve salt tolerance of crops.